Sperm traits differ between winged and wingless males of the ant Cardiocondyla obscurior. Issue 6 (November 2016) - SCHREMPF, Alexandra; MOSER, Astrid; DELABIE, Jacques; HEINZE, Jürgen
Abstract: Size and shape of sperm cells vary tremendously throughout the animal kingdom. The adaptive significance of this variation is not fully understood. In addition to sperm–female interactions and the environmental conditions, the risk of sperm competition might affect number, morphology and other "quality" traits of sperm. In the male‐diphenic ant Cardiocondyla obscurior, winged sneaker males have limited sperm number, because their testes degenerate shortly after adult emergence, as is typical for males of social Hymenoptera. In contrast, wingless fighter males continuously replenish their sperm supply due to their exceptional lifelong spermatogenesis. While winged males usually have to compete with several other winged males for virgin queens, wingless males are able to monopolize queens by killing all other rivals. Hence, this presents a unique system to investigate how alternative reproductive tactics and associated physiology affect sperm morphology and viability. We found that sperm‐limited males invest into sperm number instead of sperm size. Variance in sperm length is smaller in winged males, probably reflecting that they have to compete with several other males. Finally, sperm viability is equally high in both male phenotypes.